Breached Barriers: A Scoping Review of Blood-Central Nervous System Barrier Pathology in Amyotrophic Lateral Sclerosis - Mirian, Ario; Moszczynski, Alexander; Soleimani, Serena; Aubert, Isabelle; Zinman, Lorne; Abrahao, Agessandro (Frontiers in Cellular Neuroscience, 2022)
Recent studies have implicated changes in the blood-central nervous system barriers (BCNSB) in amyotrophic lateral sclerosis (ALS). The objective of this scoping review is to synthesize the current evidence for BCNSB structure and functional abnormalities in ALS studies and propose how BCNSB pathology may impact therapeutic development. Methods: A literature search was conducted using Ovid Medline, EMBASE, and Web of Science, from inception to November 2021 and limited to entries in English language. Simplified search strategy included the terms ALS/motor neuron disease and [BCNSB or blood-brain barrier (BBB) or blood-spinal cord barrier (BSCB)]. Henceforth, BCNSB is used as a term that is inclusive of the BBB and BSCB. Four independent reviewers conducted a title and abstract screening, hand-searched the reference lists of review papers, and performed a full text review of eligible studies. Included studies were original peer-reviewed full text publications, evaluating the structure and function of the BCNSB in preclinical models of ALS, clinical ALS, or postmortem human ALS tissue. There was no restriction on study design. The four reviewers independently extracted the data. Results: The search retrieved 2,221 non-duplicated articles and 48 original studies were included in the synthesis. There was evidence that the integrity of the BCNSB is disrupted throughout the course of the disease in rodent models, beginning prior to symptom onset and detectable neurodegeneration. Increased permeability, pharmacoresistance with upregulated efflux transporters, and morphological changes in the supporting cells of the BCNSB, including pericytes, astrocytes, and endothelial cells were observed in animal models. BCNSB abnormalities were also demonstrated in postmortem studies of ALS patients. Therapeutic interventions targeting BCNSB dysfunction were associated with improved motor neuron survival in animal models of ALS. Conclusion: BCNSB structural and functional abnormalities are likely implicated in ALS pathophysiology and may represent an upstream to neurodegeneration. Promising therapeutic strategies targeting BCNSB dysfunction have been tested in animals and can be translated into ALS clinical trials.